2022
DOI: 10.15252/emmm.202114841
|View full text |Cite
|
Sign up to set email alerts
|

Promoters of ASCL1‐ and NEUROD1‐dependent genes are specific targets of lurbinectedin in SCLC cells

Abstract: Small-Cell Lung Cancer (SCLC) is an aggressive neuroendocrine malignancy with a poor prognosis. Here, we focus on the neuroendocrine SCLC subtypes, SCLC-A and SCLC-N, whose transcription addiction was driven by ASCL1 and NEUROD1 transcription factors which target E-box motifs to activate up to 40% of total genes, the promoters of which are maintained in a steadily open chromatin environment according to ATAC and H3K27Ac signatures. This leverage is used by the marine agent lurbinectedin, which preferentially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…23,24 Recent studies have reported on the potential effects of targeted therapies, such as aurora kinase inhibitors and lurbinectedin, in NEUROD1-dominant SCLC. 23,25 In contrast, NEUROD1 has not been studied in CSCNEC so far. Considering that NEUROD1-dominant CSCNEC shows similar clinical behavior to SCLC, the application of targeted therapies for NEUROD1-dominant SCLC could be considered in CSCNEC with further accumulation of supporting evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Recent studies have reported on the potential effects of targeted therapies, such as aurora kinase inhibitors and lurbinectedin, in NEUROD1-dominant SCLC. 23,25 In contrast, NEUROD1 has not been studied in CSCNEC so far. Considering that NEUROD1-dominant CSCNEC shows similar clinical behavior to SCLC, the application of targeted therapies for NEUROD1-dominant SCLC could be considered in CSCNEC with further accumulation of supporting evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In SCLC, the NEUROD1-dominant subtype was shown to be associated with extensive disease and poor prognosis by promoting tumor cell migration through tyrosine kinase tropomyosin-related kinase B and neural cell adhesion molecule, which are pro-metastatic signaling molecules 23,24 . Recent studies have reported on the potential effects of targeted therapies, such as aurora kinase inhibitors and lurbinectedin, in NEUROD1-dominant SCLC 23,25 . In contrast, NEUROD1 has not been studied in CSCNEC so far.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulating the tumor progression, NEUROD1 could be also a drug target in cancer therapy. In small-cell lung cancer, NEUROD1-dependent genes are specific targets of lurbinectedin ( Costanzo et al, 2022 ). Moreover, NEUROD1 could be used as a marker for efficacy monitoring as well.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that CS proteins participate in RNA pol I and II mediated basal and activated transcription ( Balajee et al, 1997 ; Selby and Sancar, 1997 ; Bradsher et al, 2002 ; Yuan et al, 2007 ; Brooks et al, 2008 ; Koch et al, 2014 ; Lanzafame et al, 2021 ). In this context, it is worth noting the role of CSB in the transcriptional activation of some key genes, as neuroD1 ( Ciaffardini et al, 2014 ), whose tight regulation is well known to be required to avoid the trigger of dysregulatory mechanisms for initiating and promoting oncogenic activities ( Costanzo et al, 2022 ). For this reason, it might be of interest investigating if CSB overexpression is causative for the abnormal regulation of these key genes and, consequently, for the induction of the hyperactivation cascades aimed to direct cell fate towards abnormal survival and proliferation.…”
Section: The Unbalance Of Cs Proteins In Aging and Cancermentioning
confidence: 99%